Risk management - Moroz, Volodymyr M.; Buka, Inta; Moroz, Svitlana A.; Trush, Oleksandr Olehovych; Moroz, Oleksandr ("Novyi Svit – 2000", 2024)
The content of the manual contributes to students' formation of coherent and logically consistent system of knowledge about the theory and practice of risk management. The manual reveals the dependence of the effectiveness and performance of organizational activities on the level of theoretical knowledge of the management subject concerning the content and practice of implementing risk minimization mechanisms, as well as the ability to use them within the risk management system. The manual is designed for students studying the speciality specialties 054 – Sociology, 281 – Public Administration and Governance of both full-time and part-time education.
Keywords: manual; risk management; management; management activities; system of organization's general management; narrow-profile direction